Product differentiation strategy and vertical integration: an application to the DOC Rioja wine industry - Fernández-Olmos, Marta; Dejo-Oricain, Natalia; Rosell-Martínez, Jorge (Journal of Business Economics and Management, 2016)
This study evaluates the importance of product differentiation as a determinant of vertical integration in firms. The proposed model also controls for known determinants of integration, such as transaction costs and firm-level capabilities. By identifying transaction-, firm- and strategy-level determinants, we derive testable predictions about the vertical integration decision. To test these predictions we analyze the Rioja wine industry, using a representative sample of 187 firms. Our paper concludes that reaching judicious vertical integration decisions requires a thorough analysis of some very diverse aspects, especially those related to mitigating opportunism, dealing with unforeseen contingencies and product differentiation.